2015
DOI: 10.1002/cjp2.25
|View full text |Cite
|
Sign up to set email alerts
|

Classical pathology and mutational load of breast cancer – integration of two worlds

Abstract: Breast cancer is a complex molecular disease comprising several biological subtypes. However, daily routine diagnosis is still based on a small set of well‐characterized clinico‐pathological variables. Here, we try to link the two worlds of surgical pathology and multilayered molecular profiling by analyzing the relationships between clinico‐pathological phenotypes and mutational loads of breast cancer. We evaluated the number of mutated genes with somatic non‐silent mutations in different subgroups of breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
64
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 56 publications
5
64
1
Order By: Relevance
“…TIL density is a crucial surrogate reflecting immune responsiveness to tumor peptide. TNBC is more densely infiltrated with lymphocytes than other subtypes 23, which may be partly explained by its high genetic instability and mutational load 24, 25. Aberrant proteins, termed neoantigens, encoded by mutated genes are more likely recognized by T cells as foreign than are non-mutant proteins and may provoke a more brisk lymphocytic reaction 26.…”
Section: Discussionmentioning
confidence: 99%
“…TIL density is a crucial surrogate reflecting immune responsiveness to tumor peptide. TNBC is more densely infiltrated with lymphocytes than other subtypes 23, which may be partly explained by its high genetic instability and mutational load 24, 25. Aberrant proteins, termed neoantigens, encoded by mutated genes are more likely recognized by T cells as foreign than are non-mutant proteins and may provoke a more brisk lymphocytic reaction 26.…”
Section: Discussionmentioning
confidence: 99%
“…As matching tissue material harbored the very same genetic aberrations, these are high‐confidence results that may also support pathological tumor typing. With respect to diagnostic applications, detection of, for example, CDH1 mutations can aid conventional cytology and IHC in diagnosing lobular breast carcinoma . A patient in our cohort (c5), who was initially diagnosed with metastatic papillary thyroid cancer at a secondary care hospital, eventually developed ascites and peritoneal carcinomatosis.…”
Section: Discussionmentioning
confidence: 99%
“…23 With many more drugs in the pipeline of various pharmaceutical companies, solving this issue will become increasingly important. While genetic parameters, 24 such as PD-L1 amplification, 25,26 mutational burden, [27][28][29][30][31] mutated POLE, 32,33 and microsatellite instability 34 as well as specific immune cell compositions 35 can identify patients that benefit from checkpoint blockade, recent data demonstrated that specific mutations in B2M, JAK1 and JAK2 occurring either de novo during therapy or already being present in treatment-naïve melanoma or colorectal cancer confer resistance to pembrolizumab. 36,37 Albeit the number of cases was low in both studies, these reports strongly suggest that negative response predictors are available that could directly complement stratifiers currently in use.…”
mentioning
confidence: 99%